Enhancing Faculty Work Productivity through Organizational Support and Servant Leadership with the Mediating Role of Work Motivation: A Study Case at University of Muhammadiyah Jakarta - Andriansyah, Muhammad; Rubini, Bibin; Setyaningsih, Sri (PPSDP International Journal of Education, 2024)
This study aims to examine the influence of organizational support and servant leadership on work productivity, both directly and indirectly through work motivation as a mediating variable. A quantitative approach with a survey method was employed by involving 164 permanent faculty members of the University of Muhammadiyah Jakarta as the sample. Data collection techniques was conducted using questionnaires, and path analysis was performed for data analysis. The results indicate that organizational support (β = 0.309), servant leadership (β = 0.375), and work motivation (β = 0.149) have a direct positive, and significant influence on work productivity. Additionally, organizational support (β = 0.338) and servant leadership (β = 0.303) also exert a direct positive and significant influence on work motivation. Work motivation mediates the relationship between organizational support (β = 0.050) and servant leadership (β = 0.045) on work productivity, although this mediating influence is less effective than the direct influences, which are more dominant. The findings offer recommendations for faculties and stakeholders to enhance work productivity in achieving the Three Principles (Tri Dharma) of Higher Education through strategies that strengthen organizational support, servant leadership, and work motivation.